(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. Bone disease and bone fractures are common among kidney transplant recipients. The aim of this study was to investigate the prevalence of vitamin D deficiency, hyperparathyroidism, and osteoporosis kidney transplant patients. Materials and Methods. A total of 113 kidney transplant recipients (58 women and 55 men) were selected consecutively from the transplant clinic between January and April 2010. A serum sample from each patient was analyzed for creatinine, calcium, phosphorus, 25-hydroxyvitamin D, and intact parathyroid hormone levels. Bone mineral density was measured by the dual energy x-ray absorptiometry method and classified according to the classification of the World Health Organization. Risk factors of bone mineral density outcomes were evaluated in univariable and multivariable analyses. Results. Forty-five percent of the patients had vitamin D deficiency and 76.2% had hyperparathyroidism. There was a significant correlation between vitamin D deficiency and high serum parathyroid hormone (P = .04) and serum creatinine levels (P = .001). However, there were no significant associations of serum calcium and phosphorus with vitamin D or parathyroid hormone levels. The osteoporosis and osteopenia were reported in 12.4% and 52.2% of the recipients in the lumbar spine and 45.1% and 36.3% of the patients in the femoral neck, respectively. Multivariable analyses showed that there were significant correlations between patients’ age and body mass index and femoral neck osteoporosis. Risk factors for lumbar spine osteoporosis were end-stage renal disease duration, serum calcium, and body mass index. Conclusions. Vitamin D deficiency, hyperparathyroidism, and osteoporosis are very common in our kidney transplant recipients. Early diagnosis and treatment of these abnormalities should be included in the posttransplant follow-up of patients in order to prevent severe bone diseases and bone fractures.